Trimma tevegae and T. caudomaculatum revisited and redescribed (Acanthopterygii, Gobiidae), with descriptions of three new similar species from the western Pacific - Winterbottom, Richard (Zootaxa, 2016)
A redescription and diagnosis of Trimma tevegae, based on 50 additional specimens from the type locality at Rabaul, New Britain is provided, and contrasted with the redescription and diagnosis of T. caudomaculatum, based on the type material and an additional 22 specimens from various western Pacific localities. Trimma tevegae may most easily be recognized by the lack of a blue stripe (dark in preservative) in the dorsal midline of the snout, and a short second spine in the first dorsal fin, reaching posteriorly to the origin or first few ray bases of the second dorsal fin. Trimma caudomaculatum can be identified by the blue stripe from the snout along the dorsal midline, the blue spots and stripes in front of the eye, on the opercle and beneath the eye (dark in preserved material), and the very elongate second dorsal spine, usually extending to beyond the end of the second dorsal fin. Three similar-looking new species are described. Trimma burridgeae and T. hollemani are morphologically very close to each other, differing mainly in the length of the second dorsal spine (to the posterior base of the second dorsal fin or beyond in T. burridgeae; to the anterior base of that fin in T. hollemani). These two species differ by over 9% of the bases of the COI gene. Trimma corerefum is the most distinctive of the species, differing in lacking a blue stripe on the dorsal surface of the snout, in the pigment pattern around the eye, in having fewer cephalic sensory papillae (free neuromasts) in rows dʹ, ea, ep, f, r and ot, and in a shorter fifth pelvic fin ray (34–45% length of fourth pelvic ray). The morphological differences between the species are reinforced by the results of a barcode analysis of the COI gene, based on 105 specimens.